N6-methyladenosine of chromosome-associated regulatory RNA regulates chromatin state and transcription. - Liu, J.; Dou, X.; Chen, C.; Chen, C.; Liu, C.; Xu, M. M.; He, C.
N6-methyladenosine (m6A)is the most abundant messenger RNA modification in almost all eukaryotes. Liu et al. now show that m6A is also cotranscriptionally added onto various chromosome-associated regulatory RNAs (carRNAs)in mammalian cells. Disruption of m6A modification of these RNAs increases their abundance and promotes gene transcription by increasing the chromatin accessibility. Thus, m6A serves as a switch to regulate carRNA levels by tuning nearby chromatin state and downstream transcription.
Keywords: RNA REGULATES CHROMATIN; TRANSCRIPTION